If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(a + -3) + -1(1 + -6a) = 7a + -4a Reorder the terms: 8(-3 + a) + -1(1 + -6a) = 7a + -4a (-3 * 8 + a * 8) + -1(1 + -6a) = 7a + -4a (-24 + 8a) + -1(1 + -6a) = 7a + -4a -24 + 8a + (1 * -1 + -6a * -1) = 7a + -4a -24 + 8a + (-1 + 6a) = 7a + -4a Reorder the terms: -24 + -1 + 8a + 6a = 7a + -4a Combine like terms: -24 + -1 = -25 -25 + 8a + 6a = 7a + -4a Combine like terms: 8a + 6a = 14a -25 + 14a = 7a + -4a Combine like terms: 7a + -4a = 3a -25 + 14a = 3a Solving -25 + 14a = 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. -25 + 14a + -3a = 3a + -3a Combine like terms: 14a + -3a = 11a -25 + 11a = 3a + -3a Combine like terms: 3a + -3a = 0 -25 + 11a = 0 Add '25' to each side of the equation. -25 + 25 + 11a = 0 + 25 Combine like terms: -25 + 25 = 0 0 + 11a = 0 + 25 11a = 0 + 25 Combine like terms: 0 + 25 = 25 11a = 25 Divide each side by '11'. a = 2.272727273 Simplifying a = 2.272727273
| 3/31.5= | | 6k-25=7-3k | | 3/10p=9 | | -4=-3x+2 | | -3x+5(6x-7)=-35+2x | | u^2-13u+40=0 | | (4j+8)-3=92 | | 12-(2m+4)=2+2m-14 | | 3m-4m-5m= | | 2(y+5)=2(6y-1)+4y | | m+3m+7m+4= | | -7(6n+7)=-91 | | x-7/5=x-2/3 | | 50=3.14*2*h+3 | | -2c^2-8=56-3c | | 10x-21=5x+9 | | u^2-13u+4=0 | | 7*N=-147 | | -10+4(3p+10)=-1 | | 3.14*2*h+3=50 | | -10+4(3p+6)=-1 | | -4(1-4x)-8x=-2(x+7) | | 7(14x^2+5x-1)=0 | | 1b/13-9b/13=64/13 | | m(3.8)=9(4)-9(m) | | 9=9n | | -2t+3/2=t/4-12 | | 0.94x+0.98(18-x)=17.28 | | 5/2t=10 | | 2x(-6x)= | | -10+4(j+6)=-1 | | 12(6x+4)=x+2(x+1) |